Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1444-0938.2009.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cycloplegia on axial length and anterior chamber depth measurements in children

Abstract: Background:Cycloplegia has been shown to have no effect on axial length measurement made with the IOLMaster in adults. The current study aimed at evaluating the effect of cycloplegia on axial length and anterior chamber depth (ACD) measurements made with the IOLMaster and an ultrasonic biometer in children. Methods: Pre-and post-cycloplegic axial length and ACD were measured with the IOLMaster followed by the Sonomed A-5500 in 31 children aged from seven to 15 years by the same examiner. The 95% limits of agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 18 publications
(71 reference statements)
7
44
0
Order By: Relevance
“…Sheng et al [8] found that cycloplegia had no significant effect on IOL Master AL measurements but produce a significant increase in ACD as measured with the IOLMaster. Cheung [9] found that the effect of cycloplegia on AL measurement with IOLmaster was insignificant in children aged from seven to 15 years; meanwhile, ACD measurement was significantly affected by cycloplegia. Huang et al [10] found that cycloplegia This device has also been found to provide repeatable, reproducible measurements and can be used interchangeably with Sirius (Scheimpflug camera and Placido-disk topography device) for CCT, ACD, mean K, and WTW [11].…”
Section: Discussionmentioning
confidence: 97%
“…Sheng et al [8] found that cycloplegia had no significant effect on IOL Master AL measurements but produce a significant increase in ACD as measured with the IOLMaster. Cheung [9] found that the effect of cycloplegia on AL measurement with IOLmaster was insignificant in children aged from seven to 15 years; meanwhile, ACD measurement was significantly affected by cycloplegia. Huang et al [10] found that cycloplegia This device has also been found to provide repeatable, reproducible measurements and can be used interchangeably with Sirius (Scheimpflug camera and Placido-disk topography device) for CCT, ACD, mean K, and WTW [11].…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, we only analyzed the postcycloplegic ACD in all subjects. A previous study found that the ACD could be increased by 0.05 to 0.06 mm after cycloplegia [23] but as our population consisted of children aged 4 to 18, the accommodative power would vary considerably; thus, the authors decided that using a standardized postcycloplegic ACD measurement in all subjects would bring more consistency to our comparisons. Thirdly, the association between ACD and the inferior and global RNFL was only a weak correlation, and larger scale studies are warranted to establish the clinical significance of such association.…”
Section: Discussionmentioning
confidence: 99%
“…Since the sub-foveal choroid increased in thickness by 14 μm and the axial length decreased by 6 μm 60 minutes after homatropine instillation, the unaccounted 8 μm may be the result of the biomechanical forces on the globe associated with ciliary muscle relaxation and changes in the iris that also led to significant deepening of the anterior chamber and lens thinning. Previous animal (Nickla and Schrödl, 2012;Lin et al, 1996;Schmid and Wildsoet, 1996) and human (Drexler et al, 1997;Cheung et al, 2009) studies have also reported a significant variation in the anterior chamber depth and lens thickness measurements after the administration of muscarinic antagonists or surgical modification of parasympathetic input to the eye, with trends similar to the results obtained in our study. Pharmacologic blockade of cholinergic transmission resulted in significant enlargement of anterior chamber depth and thinning of the lens.…”
Section: Discussionsupporting
confidence: 81%